IDENTIFICATION OF MEDICINAL PLANT VARIATIONS AND THEIR UTILIZATION BY RURAL AND URBAN COMMUNITIES IN MOJOGEDANG DISTRICT, KARANGANYAR - Manullang, Raymond Hamonangan; Sari, Yulia Dinda; Rasyida, Zahratushahwah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Medicinal plants are types of flora containing active compounds beneficial for preventing, treating, or alleviating various diseases. These plants are often used as part of traditional medicine practices across different cultures worldwide. This study aims to explore the diversity of medicinal plants and their utilization by rural and urban communities in Mojogedang Subdistrict, Karanganyar. The research employed a purposive snowball sampling method, with data collection techniques including observation, semi-structured interviews, and in-depth interviews. The collected data were analyzed using qualitative and quantitative approaches. Based on the study results, 31 species of medicinal plants were identified as being used regularly by the community. The most commonly used species belong to the family Zingiberaceae. Both rural and urban communities predominantly utilize the leaves of medicinal plants for treating illnesses. The findings conclude that utilizing medicinal plants as a natural health resource can support the sustainability of traditional medicine while also meeting modern healthcare needs in the community.